2014
DOI: 10.1007/s12032-014-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed plus dendritic cells as second-line treatment for patients with stage IIIB/IV non-small cell lung cancer who had treatment with TKI

Abstract: The aim of this study was to determine the efficacy and toxicity of pemetrexed plus dendritic cells (DCs) in patients suffering from stage IIIB or IV lung adenocarcinoma, who had undergone maintenance treatment with gefitinib or erlotinib. Patients who had failed gefitinib or erlotinib maintenance treatment had ECOG performance statuses ranging from 0 to 2.27 patients received pemetrexed plus DCs as second-line treatment. Dosage: 500 mg/m(2) pemetrexed was administered on day 1 of a 21-day cycle. DCs were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…A pilot study loaded autologous DCs with a cocktail of tumor peptides including WT1, CEA, MAGE‐1, and HER‐2, however, because of its small size, the results are not reliable (Perroud et al, ). Moreover, several studies for loading DCs have used the tumor lysates (Hu et al, ; Um et al, ). Tumor lysates are cocktails of the tumor and normal antigens to enhance possibility of autoimmune diseases and harmful immunological reactions in patients with advanced lung with chemo‐immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot study loaded autologous DCs with a cocktail of tumor peptides including WT1, CEA, MAGE‐1, and HER‐2, however, because of its small size, the results are not reliable (Perroud et al, ). Moreover, several studies for loading DCs have used the tumor lysates (Hu et al, ; Um et al, ). Tumor lysates are cocktails of the tumor and normal antigens to enhance possibility of autoimmune diseases and harmful immunological reactions in patients with advanced lung with chemo‐immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al investigated the efficacy and safety of pemetrexed plus DCs cocultured autologous tumor lysates in 27 patients with locally advanced or metastatic lung adenocarcinoma after the failure of gefitinib or erlotinib first‐line treatment. Although this study did not evaluate the adverse effects of pemetrexed/DCs and not divide patients into control and therapy groups, however, they showed that patients with Stage IIIB or IV lung adenocarcinoma who had received gefitinib or erlotinib maintenance therapy responded well to this therapeutic regimen such that the progression‐free survival was 4.5 months, and OS 10.5 months (Hu et al, ). Considering the tumorigenesis of myeloid‐derived suppressor cells (MDSCs) in tumor microenvironments and limiting the efficacy of immunotherapy, Iclozan et al designed a randomized clinical trial on 41 patients with extensive stage SCLC.…”
Section: Dendritic Cells and Lung Cancer Immunotherapiesmentioning
confidence: 99%
“…For NSCLC, this synergistic effect of both chemotherapy and radiotherapy with DC vaccination was confirmed in mouse models ( 45 47 ). In human NSCLC, only one study examined the combination of chemotherapy with DC monotherapy, but many studies investigated the combined effect of chemo- and/or radiotherapy, DC vaccination and cytokine-induced killer cells (CIK) ( Table 2 ) ( 48 , 50 55 ). CIK cells consist of a heterogeneous group of T cells, NK cells, and NKT cells.…”
Section: Vaccination Combination Therapies For Nsclcmentioning
confidence: 99%
“…)(48,(50)(51)(52)(53)(54)(55). CIK cells consist of a heterogeneous group of T cells, NK cells, and NKT cells.…”
mentioning
confidence: 99%
“…It is a multitargeted antifolate medicine that has been widely used in maintenance treatment for patients with advanced NSCLC (Kato et al, 2014). It reduces the proliferation of cancer cells, thus inhibiting further progression of NSCLC in the patient’s body (Hu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%